2021
DOI: 10.3389/fnagi.2021.646908
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Regional Damage Detected by Neuroimaging and Neuropathological Studies in Older Adults With COVID-19: A Cognitive-Neuroscience Systematic Review to Inform the Long-Term Impact of the Virus on Neurocognitive Trajectories

Abstract: Background: Other than its direct impact on cardiopulmonary health, Coronavirus Disease 2019 (COVID-19) infection affects additional body systems, especially in older adults. Several studies have reported acute neurological symptoms that present at onset or develop during hospitalisation, with associated neural injuries. Whilst the acute neurological phase is widely documented, the long-term consequences of COVID-19 infection on neurocognitive functioning remain unknown. Although an evidence-based framework de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 127 publications
(370 reference statements)
2
61
0
Order By: Relevance
“…org/10.21203/rs.3.rs-1139035/v1), or of virus-induced neuroinflammation [3][4][5] (https://doi.org/10.1101/2021.02. 23.432474): neurological and cognitive deficits demonstrated by patients 6,7 , with an incidence of neurological symptoms in more than 80% of the severe cases 8 , radiological and post mortem tissue analyses demonstrating the impact of COVID-19 on the brain 9,10 , and the possible presence of the coronavirus in the central nervous system found in some studies [11][12][13] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…org/10.21203/rs.3.rs-1139035/v1), or of virus-induced neuroinflammation [3][4][5] (https://doi.org/10.1101/2021.02. 23.432474): neurological and cognitive deficits demonstrated by patients 6,7 , with an incidence of neurological symptoms in more than 80% of the severe cases 8 , radiological and post mortem tissue analyses demonstrating the impact of COVID-19 on the brain 9,10 , and the possible presence of the coronavirus in the central nervous system found in some studies [11][12][13] .…”
mentioning
confidence: 99%
“…There is strong evidence for brain-related abnormalities in COVID-19 [1][2][3][4][5][6][7][8][9][10][11][12][13] . It remains unknown however whether the impact of SARS-CoV-2 infection can be detected in milder cases, and whether this can reveal possible mechanisms contributing to brain pathology.…”
mentioning
confidence: 99%
“…According to this retrospective review in a predefined period of inclusion, the mild-to-moderate and severe hypometabolic long-COVID patterns represent 47% of patients. Other studies involving long-COVID patients found hypometabolism mainly in the fronto-orbital regions [ 9 , 10 ] or a similar long-COVID pattern on MRI scans with a more pronounced reduction in grey matter thickness and contrast in the orbitofrontal cortex and parahippocampal gyrus, as well as involvement of the brainstem region [ 2 , 3 ]. This also means that the previously reported hypometabolic pattern is not visually found in all patients with suspected neurological long COVID.…”
Section: Discussionmentioning
confidence: 93%
“…In such suspected cases, patients can be referred to the Nuclear Medicine Departments for brain 18 F-FDG PET scans to contribute to the workup of a differential diagnosis, and to potentially identify the hypometabolic pattern previously reported at the group level in a recent monocentric study for this new entity involving fronto-orbital olfactory regions and other limbic/paralimbic regions, as well as the brainstem and cerebellum [ 4 ]. Brain areas that composed this hypometabolic pattern have also been reported in an MRI study measuring cortical atrophy before and after COVID infection [ 2 ], as well as in a review of ninety studies [ 3 ]. Validation of this long-COVID hypometabolic PET pattern is consequently needed at the individual and multicentric levels to easily apply it in clinical routine for nuclear physicians.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation